Hubungan Tingkat Pengetahuan Ibu Tentang Stimulasi Perkembangan Kognitif Anak Terhadap Status Perkembangan Kognitif Anak Usia Prasekolah - Miranda Dwi yana (Sekolah Tinggi Ilmu Kesehatan Hang Tuah Surabaya, 2026)
Introduction: the cognitive development of preschool-aged children is an essential aspect of grouwth and development, influenced by environmental stimulation particularly the role of mother as primary caregivers. limited maternal knowledge regarding cognitive stimulation may lead to developmental delays in children. Objective: this syudy aimed to determine the relationship between mothers knowledge of cognitive development stimulation and the cognitive status of preschool-aged children at TK Aisyiyah VII, Payung Sekaki District, Pekanbaru. Methods: this research employed a quantitave approach with a descriptive correlational design and a crosssectional method. the study involed 86 respondents (mathers with preschool-aged children) selected using a total sampling technique. data were collected using questionaires on mothers knowledge of cognitive stimulation and preschool children's cognitive development. data analysis was performed using the Chi-Square test. Result: most mostehrs had a low level of knowledge accounting for 33 respondent (38,4%), while the majority of choldrens cognitive development status fell into the fair and poor categories, totaling 62 respondents (72%). the statistical test showed a significant relationship development status of preschool-aged children (p-value = 0,000 < 0,05. mother's knowledge significantly influences the cognitive development of preschool-aged children. conclusions: this study can serve as a reference for healthcare professionals to provide education, guidances, and support to mothers in delivering appropriate cognitive stimulation to ensure optimal child growth and development.